As tecnologias digitais no espaço acadêmico como instrumentos na construção do conhecimento do design de moda - Nascimento, Nelymar Gonçalves do (Universidade do Vale do Rio dos Sinos, 2014)
This research focuses on the development of knowledge in the field of fashion through the use of digital technologies, taking students as subjects in their everyday academic environment. This study aims to analyze the use of digital technologies as a means and end of the learning method for the development of creative skills of the student. To this end, we attempted to check: a) physical structure provided to these students by the university; b) the teaching methodologies used within these technologies, as well as, c) the perception of acclimated or not with the technologies students. This research was based on the socio-historical Vygotsky’s theory about the construction of knowledge, in which the subject is psychologically and cognitively in interaction with their social group for mediating instruments and relationships established throughout history. The method employed for the production of the data was used in the interview discussion groups and content analysis technique for reading comprehension thereof. It is considered that students learning of the course builds researched not only in the interaction with the machine and its software, but also the participation of their classmates and teachers through interaction provided by commitment in carrying out their activities. This mediation process leads to stimulating the potential development of essential features to fashion design.
Keywords: Construção do conhecimento; Mediação em Vigotsky; Tecnologias digitais; Design de moda; Knowledge building; Mediation Vygotsky; Digital technology; Fashion design; ACCNPQ::Ciências Humanas::Educação